2022
DOI: 10.1371/journal.pone.0278173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-course point-of-care echocardiography training on the performance of medical interns in children

Abstract: Background Point-of-care ultrasound (POCUS) can add complementary information to physical examination. Despite its development in several medical specialties, there is a lack of similar studies on children by medical interns and cardiologists. Therefore, investigators aimed to assess the effect of short-course training on the performance of medical interns in point-of-care echocardiography in children. Methods This analytic cross-sectional study was conducted on 161 hospitalized children in 17 Shahrivar chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Compared to these techniques, the IVC collapsibility index may be favorable in clinical practice. Furthermore, a study reported that this technique is easy to perform [41], indicating its feasibility in clinical practice. The strength of our metaanalysis lies in its inclusion of a diverse patient population, including those undergoing both cesarean section and non-cesarean section procedures, supporting its generalizability to a wider range of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to these techniques, the IVC collapsibility index may be favorable in clinical practice. Furthermore, a study reported that this technique is easy to perform [41], indicating its feasibility in clinical practice. The strength of our metaanalysis lies in its inclusion of a diverse patient population, including those undergoing both cesarean section and non-cesarean section procedures, supporting its generalizability to a wider range of patients.…”
Section: Discussionmentioning
confidence: 98%